Cloud-to-ground lightning observations over the Eastern Amazon region: Subsidies for the protection of electric systems - Almeida, Arthur C.; Rocha, Brigida R. P.; de Souza, Jose R. S.; Monteiro, Jose H. A.; Sa, Jose A. S. (2010 30th International Conference on Lightning Protection (ICLP), 2010)
Cloud-to-ground (CG) lightning variables, space and time distributions near the equator, over Eastern Amazon, were analyzed in this work. Over seven million lightning flash events of this type, detected by a VAISALA sensor network operated by the Brazilian Amazon Protection System (SIPAM) between 2006 and 2008 were processed. The results show the sub-areas of higher frequency of occurrences, as well as the monthly and hourly distributions of CG lightning polarity type, current peak intervals for this region. The regional values of the CG lightning parameters should be taken into consideration on electric and telecommunication systems protection projects, against atmospheric electric discharges in the Amazon Region.